Semi microscopic description of 84 Kr - Dias, Hélio (1986)
The experimental information on the84Kr nuclei is compared with the model calculation in which two neutron holes are coupled to the vibrational field. Based on the lower-order terms of a perturbative expansion of the E2 and M1 transition matrix elements, a simple rule is obtained for the sign and the magnitude of theδ (E2/M1) ratios for the transitions between the second and first 2+ states in some vibrational nuclei.